An exploration of the distractions inherent to social media use among athletes. Issue 5 (November 2020) - Hayes, Michelle; Filo, Kevin; Geurin, Andrea; Riot, Caroline
Highlights: Positive and negative commentary presents distractions to athletes. Social media can used to manage the moods of athletes during events. Athletes engage in self-awareness to address social media distractions. Developing athlete coping and mental skills could assist in minimising distractions. Abstract: Social media present athletes with a number of benefits and challenges. As a result, various sport stakeholders have debated appropriate social media use among athletes at major sport events, with some suggesting that using these platforms can have negative consequences. The purpose of this research was to examine the elements of social media that athletes perceive to be distracting during major sport events and the practices they undertake to address such distractions. Interviews with Australian elite athletes ( N  = 15) were conducted and data were analysed using thematic analysis. The findings reveal several elements associated with distraction, including positive and unwanted messages, branding pressures, and competitor content. Athletes reported two key practices that assisted in overcoming distractions, including switching off and handing over the control of their social media accounts. The findings extend distraction-conflict theory to athlete social media research, while presenting a preliminary conceptual model to assist researchers in further understanding the potential impact of social media distractions on athletes. Opportunities for sport practitioners to develop or implement social media education programs are described.